(untitled) (International Journal of Physiotherapy, 2021)
Background: Returning to safe driving is an essential aspect of the rehabilitation following total hip (THR) or total knee replacement (TKR). Making an emergency stop has been used in the past as the main criteria to assess fitness to drive following surgery. Methods: We have tested the Total Brake Reaction Time (TBRT) before surgery and at different intervals post-surgery (1,2,4 and 6 weeks) using a driving simulator. A return to baseline TBRT was used as the criteria for safe driving status. Results: Overall, 22 patients (11 males and 11 females), 14 in the THR and 8 in the TKR group. The median recovery time for the THR group was two weeks compared to 4.4 weeks for the TKR group (p<0.034). The overall failure rate of return to baseline was 14.3% for THRs and 62.5% for TKRs. Females had a significantly slower mean baseline TBRT (504ms) compared to males (414ms) (p<0.046) but had a faster median recovery time of 2 weeks compared to 3.3 weeks for males (p<0.72). However, we found a higher failure rate of return to baseline of 45.5% for females compared to 18.2% for males. Conclusion: Due to a wide variation in the recovery of safe driving ability, we recommend that patients refrain from driving for 2-4 weeks following a hip replacement and 6-8 weeks following a knee replacement.